Confidence in Knowledge or Confidence in the Ability to Learn: An Experiment on the Causal Effects of Beliefs on Motivation - Mira Fischer; Dirk Sliwka (Institute of Labor Economics (IZA), 2018)
Previous research has shown that feedback about past performance has ambiguous effects on subsequent performance. We argue that feedback affects beliefs in different dimensions â exteuro“ namely beliefs about the level of human capital and beliefs about the ability to learn â exteuro“ and this may explain some of the ambiguous effects. We experimentally study the causal effects of an exogenously administered change in beliefs in both of these dimensions on the motivation to learn. We find that confidence in the ability to learn raises incentives, while confidence in the level of human capital lowers incentives for individuals with high levels of human capital.
Keywords: C91; D83; I21; J24; 330; human capital investment; confidence; economic experiments; motivation